A Twelve‐Year Longitudinal Analysis of Positive Youth Development Among Rural African American Males. (September 2014) - Murry, Velma M.; Berkel, Cady; Simons, Ronald L.; Simons, Leslie G.; Gibbons, Frederick X.
<x xml:space="preserve">Abstract</x> The positive youth development model was explored on a sample of 378 rural African American males to determine its usefulness in predicting HIV‐related risk behaviors. Confidence in ability to self‐regulate and sense of competence to be successful in the future were associated with having caring, involved, vigilant parents. Confident, competent males were more likely to connect with prosocial peers, which in turn provided opportunities to reinforce norms and values to dissuade and avoid engaging in risky behaviors. Growth mixture modeling results identified two subgroups with distinct developmental trajectories of risky behaviors. Group differences were associated with several components of positive youth development. Implications for future research and preventive interventions are discussed.